Martín, Marina. 2012. José Isaacson y la poética del encuentro. (Ensayo). Buenos Aires: Teseo. 236 pp. - Molina, Hebe Beatriz (2013)
Fil: Molina, Hebe Beatriz. CONICET (Consejo Nacional de Investigaciones Científicas y Técnicas) - Universidad Nacional de Cuyo